2019
DOI: 10.1021/acsabm.9b00681
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring Iridium Complexes into Crystalline Phosphorescent Nanoparticles: Structural Characterization, Photophysics, and Biological Applications

Abstract: One of the key challenges in materials science is to control the properties of a material by directing its supramolecular arrangement. Here we show that iridium complexes, such as FIrpic, Ir-PPY, and Ir-MDQ, can be organized into crystalline and phosphorescent nanoparticles through the nanoprecipitation method, which allows thorough modification of their functional properties. Moreover, we found that it is possible to combine different iridium complexes into a single multicomponent nanostructure, thus creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Palama, Di Maria, and coworkers have demonstrated that neutral iridium(III) complexes such as 63a, 66a, and 66b can self-assemble into supramolecular nanostructures through nanoprecipitation. 154 Compared to the free complexes, these NPs exhibit red-shifted emission with longer emission lifetimes. Furthermore, the NPs show reduced cytotoxic activity and enhanced cellular uptake efficiency in both 2D monolayer cells and 3D spheroids.…”
Section: Rhodium(iii)mentioning
confidence: 97%
See 1 more Smart Citation
“…Palama, Di Maria, and coworkers have demonstrated that neutral iridium(III) complexes such as 63a, 66a, and 66b can self-assemble into supramolecular nanostructures through nanoprecipitation. 154 Compared to the free complexes, these NPs exhibit red-shifted emission with longer emission lifetimes. Furthermore, the NPs show reduced cytotoxic activity and enhanced cellular uptake efficiency in both 2D monolayer cells and 3D spheroids.…”
Section: Rhodium(iii)mentioning
confidence: 97%
“…The intense emission observed in the mitochondria of human osteosarcoma cells indicates the specific accumulation and aggregation of the complex in the mitochondria after cellular uptake. Palamà, Di Maria, and co-workers have demonstrated that neutral iridium(III) complexes such as 63a , 66a , and 66b can self-assemble into supramolecular nanostructures through nanoprecipitation . Compared to the free complexes, these NPs exhibit red-shifted emission with longer emission lifetimes.…”
Section: Luminescent Transition Metal Complexes For Bioimagingmentioning
confidence: 99%
“…Typically, colloidal solutions obtained through nanoprecipitation are quite stable, even if amphiphilic surfactants or encapsulating matrices, such as sodium dodecyl sulfate (SDS), Triton X‐100, and PEG‐functionalized lipid, can be used to increase water dispersibility and to aid in stabilizing the suspension 54–56 . During NPs formation, the hydrophobic components of the surfactant/matrix are embedded into the polymeric NPs core, while the hydrophilic segments remain oriented toward the aqueous environment, that is, around the NPs shell, as a consequence of their strong interactions with water.…”
Section: Synthesis Of Semiconducting Pt‐npsmentioning
confidence: 99%
“…For example, grazing‐incidence wide‐angle X‐ray scattering experiments performed on P3HT‐NPs of different sizes have highlighted the coexistence in the nanostructure of both large crystalline domains, randomly oriented independently of the size and amorphous regions 39 . Nevertheless, the size of the crystalline domains, calculated by using the Scherrer's formula, 54,83 is closely related to the NPs size: the larger the NPs size, the larger the crystalline domain 39 …”
Section: Characterization Of Semiconducting Pt‐npsmentioning
confidence: 99%
“…In the last years, small organic phosphorescent particles have been successfully used in a variety of devices for sensing and imaging . They can be incorporated in chemical sensors or light-emitting diodes, used in O 2 sensing, , for in vivo imaging, or in phosphorescent immunoassays. , Most of the organic particles discussed in the literature contain metal complexes such as Pt­(II), Ir­(III), Eu­(III), or others. , Since the heavy metal effect induces an efficient spin–orbit coupling, they have long been used to promote organic phosphorescence. , The aim for environmentally friendly alternatives, low cost, and easy processability led to a huge effort in the preparation of small purely organic particles showing room temperature phosphorescence (RTP). Several strategies can be pursued, including H-Aggregates, encapsulation, , polymerization, , and host-guest doping. , The big advantage of RTP concerning in vivo imaging is the enhanced signal-to-noise ratio compared to fluorescence since in the afterglow emission, no luminescent background signal is present .…”
Section: Introductionmentioning
confidence: 99%